Mathematics for high school teachers : an advanced perspective - Usiskin, Zalman, ....-; Peressini, Anthony L., ....-; Marchisotto, Elena Anne, 1945- (Upper Saddle River, N.J. : Pearson Education, 2003)
Filling a wide gap in the market, this text provides current and prospective high school teachers with an advanced treatment of mathematics that will help them understand the connections between the mathematics they will be teaching and the mathematics learned in college. It presents in-depth coverage of the most important concepts in high school mathematics: real numbers, functions, congruence, similarity, and more.
INTRODUCTION. 1. What is Meant by "An Advanced Perspective"? I. ALGEBRA AND ANALYSIS WITH CONNECTIONS TO GEOMETRY. 2. Real Numbers and Complex Numbers. 3. Functions. 4. Equations. 5. Integers and Polynomials. 6. Number System Structures. II. GEOMETRY WITH CONNECTIONS TO ALGEBRA AND ANALYSIS. 7. Congruence. 8. Distance and Similarity. 9. Trigonometry. 10. Area and Volume. 11. Axiomatics and Euclidean Geometry.
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching (Secondary).; Mathematics; Wiskunde -- Secundair onderwijs